DCIR negatively regulates CpG-ODN-induced IL-1β and IL-6 production. Issue 2 (December 2015) - Zhao, Xibao; Shen, Yaping; Hu, Weiwei; Chen, Junru; Wu, Tian; Sun, Xiaoqiang; Yu, Juan; Wu, Tingting; Chen, Weilin
Highlights: CpG-ODN up-regulates DCIR expression in macrophages. DCIR inhibits CpG-ODN-induced proinflammatory cytokine production. DCIR negatively regulates CpG-ODN-induced activation of MAPK signaling. Abstract: C-type lectin receptors (CLR) are a diverse family of proteins mainly expressed on antigen-presenting cells (APC). As antigen-uptake and signaling receptors, CLR modulate immune responses of APC. The dendritic cell immunoreceptor (DCIR) is a member of CLR and has an immunoreceptor tyrosine based inhibitory motif (ITIM) in cytoplasmic tail, which is believed to play a negative role in cellular responses after antigen exposure. In addition to pathogen recognition, DCIR has been shown to be pivotal in preventing autoimmune disease by controlling dendritic cell proliferation. However, much less is known about the role of DCIR in innate immunity and its crosstalk with the Toll like receptors (TLR) pathway. In this study, we demonstrate that CpG-ODN stimulation can promote DCIR expression in macrophages and DCIR triggering inhibits the production of CpG-ODN-induced proinflammatory cytokines. We further confirm that siRNA-mediated knockdown of DCIR expression enhances CpG-ODN-induced phosphorylation of Erk1/2, JNK1/2 and p38 in macrophages. Collectively, these results indicate that DCIR is a negatively regulator in TLR9-mediated innate immune response.